Optimization of Land Use Collaborative Management Model Perum Perhutani: Study Case KPH Pekalongan Barat - Anugrah Andini Natsir; Muhamad Buce Saleh; Bahruni Bahruni (Jurnal Manajemen Hutan Tropika, 2017)
Perhutani is mandated to manage approximately 2,445,006 ha forest in Java consisting of a production forest area of 1,806,449 ha and protected forest area of 638 558 ha (Perhutani 2014). Perhutani working area consists of several units of governance in the form of Forest Management Units (KPH). Currently, 57 KPH Perhutani is experiencing various problems that the function of conservation isnot going well.  KPH Pekalongan Barat is one of the KPH which is considered quite good. It can be seen from the compliance percentage each year that reaches about 90%. The approach used in this research is 1) financial feasibility analysis, 2) land use optimization analysis, 3) multi-criteria analysis. The first analysis is financial feasibility analysis. The research's output based on the financial aspect performs that the feasibility criteria of investment of the three land use options are feasible to execute. The broad composition for optimal land use is an area covering 11,047 ha of pine, a coffee area of 2,126 ha and vegetable area 668 ha with an income of IDR872,581,112,943. According to multi-criteria analysis, the existing vegetable area is in an unfeasible area, so it can be durable.